Light environment's influence on understory sugar maple survival at and north of the current range limit. - Kwit, Matthew Casey. (Northern Illinois University.Geography., 2010)
Sorry, the full text of this article is not available in Huskie Commons. Please click on the alternative location to access it. 131 p. Sugar maple seedlings at the boreal/deciduous ecotone exist at a physiological limit. This limit is associated with low light conditions that suppress the growth of individuals. We modeled seasonal carbon assimilation by applying understory light data to light response curves. The modeled seasonal carbon gain demonstrates that seedlings gain very little carbon during the summer while the canopy is closed. Instead, seedlings rely on early spring canopy avoidance to capture a disproportionately high amount of carbon; with 80.6% of a seedling's carbon gain occurring in the first 15 days of the season. To further evaluate the importance of this gain we experimentally eliminated high spring light levels by shading seedling plots with 90% shade cloth and recorded the mortality rates for the 2009 growing season. In just one growing season, mortality rates were significantly different under each treatment, with 36% mortality recorded in control plots and 50% mortality recorded in shade plots. These two results were further tested under three unique overstory conditions that sugar maples will likely regenerate under in the future. The three overstories were: (1) sugar maple dominant, (2) sugar maple/conifer mixed, and (3) conifer dominant. Light response curves were produced and light levels were recorded for each of these locations. The mixed and boreal sites had reduced carbon budgets due to a lack of avoidance gains. This reduction in carbon gain will likely reduce survivorship, limit sugar maples' ability to develop in the boreal forest, and slow the northward migration of sugar maple at its range limit in northern Ontario.